Identification of Novel Putative Bacterial Feruloyl Esterases From Anaerobic Ecosystems by Use of Whole-Genome Shotgun Metagenomics and Genome Binning - Mogodiniyai Kasmaei, Kamyar; Sundh, John (Frontiers in Microbiology, 2019)
Feruloyl esterases (FAEs) have a wide range of applications in industry. They can be used to reduce recalcitrance of lignocellulosic biomass to enzymatic degradation and thereby to enhance utilization of lignocellulosic biomass in biorefineries or in animal feeding. In addition, ferulic acid, a product of FAE activity, has applications in pharmaceutical and food/beverage industries. It is therefore of great interest to enhance extant understanding about this enzyme family. For this purpose, we used whole-genome shotgun metagenomics and genome binning and explored rumen of dairy cows, large intestine of horses, sediment of freshwater and topsoil of forest to identify novel prokaryotic FAEs and their producing microorganisms. A number of prokaryotic genomes were recovered from which five novel bacterial FAEs were predicted. The phylogenetic analyses showed that these putative FAEs are closely related to type A FAEs and might thus possess characteristics similar to type A FAEs. We nominate Candidatus Rhabdochlamydi genus as a novel FAE producing taxonomic unit.